Analisis Peranan Audit Internal Dalam Pencegahan Fraud: Literature Review Artikel Terindeks Sinta - -, Destian Aryanti; -, Jesisca Octaviani; Natalia Priyantini; -, Resta Puji Astuti Dinah; Rachmat Agus Santoso (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Fraud is often committed by certain individuals to gain instant personal profit. The purpose of this research is to prevent fraud in various sectors by involving the role of internal auditing based on existing theories and research, enabling early identification and prevention of fraud. The research method applied in this study is qualitative descriptive method using literature review. Based on the discussion, internal auditors play a potential role in managing risks and ensuring proper governance. Effective internal audits can reduce unhealthy accounting practices that lead to fraud. Effective internal auditing is crucial in the mechanism of good governance.